QUANTUM LEARNING DALAM MENINGKATKAN KETERAMPILAN MENULIS TEKS EKSPOSISI - Andi Alfina Listya Ningrum; St. Wahidah Z; Riswan R (LPPM Universitas Muhammadiyah Bulukumba, 2022)
This is a classroom action research that aims to describe the skills of writing expository texts for class VIII1 students at SMP Negeri 6 Bulukumba through Quantum Learning. The subjects in this study were students of class VIII1, totaling 23 people. The research method used is descriptive. data research techniques through tests and observations. The data obtained were analyzed qualitatively and quantitatively. Based on data analysis, the results obtained are pada siklus I ketuntasan belajar sebesar 43,5 percent sedangkan pada siklus dua sebesar 87 percent. Based on these results, it was identified that learning to write exposition texts for class VIII1 students of SMP Negeri 6 Bulukumba by using the Quantum learning method experienced a significant increase. Thus, it can be concluded that Quantum learning is effective as one of the methods in learning to write exposition texts in class VIII1 of SMP Negeri 6 Bulukumba.